Constitution of the state of South Carolina and the ordinances, reports and resolutions adopted by the Convention of the people held in Columbia, S.C., September, 1865 (Julian A. Selby, printer to the State, 1866)
"A collection of pamphlets on the Proceedings of the Convention of the people of South Carolina, 1864-65. Contents. Constitution of South Carolina.1865. Proclamations of Governor Perry & President Johnson. Credentials of members of Convention, 1865. Reports of standing committees, 1865. Ordinances, 1865. Reports & resolutions of the General Assembly, 1865. Reports & resolutions of Session of 1864. Columbia, S.C. 1866.